25(OH)VitD and human endocrine and functional fertility parameters in women undergoing IVF/ICSI - Tian, Mei; Zeng, Suimin; Cai, Sufen; Reichetzeder, Christoph; Zhang, Xiaoli; Yin, Chenjun; Kuang, Weihong; Cheng, Kexin; Jiang, Yao; Tao, Mingqiu; Zeng, Yuan; Lin, Ge; et al. (Frontiers in Endocrinology, 2022)
Background Vitamin D plays an important role in reproduction. Evidence shown that free 25-hydroxyvitamin D (25(OH)VitD) was more accurate than total 25(OH)VitD in reflecting the status of 25(OH)VitD during pregnancy. However, the relationship between free 25(OH)VitD and female fertility parameters has not been reported yet. Therefore, this study aims to compare the correlation of free and total 25(OH)VitD with fertility parameters in infertility females undergoing in vitro fertilization and embryo transfer (IVF-ET) or intracytoplasmic sperm injection (ICSI). Methods According to the inclusion and exclusion criteria, 2569 infertility patients who received IVF-ET or ICSI treatment for the first time participated in this study. 5 ml peripheral blood samples of the patients were collected on the day before embryo transfer (ET). Enzyme linked immunosorbent assay (ELISA) kits was used to detect free 25(OH)VitD and total 25(OH)VitD, and clinical information was collected. Spearman's rho was used to evaluate the association between the variables. Results The median (IQR) of free 25(OH)VitD was 4.71 (4.11-5.31) pg/mL and total 25(OH)VitD was 19.54 (16.52-22.83) ng/m. The correlation between them, however, was week (rho=0.311). Compared to total 25(OH)VitD, free 25(OH)VitD was slightly better correlated with basal follicle-stimulating hormone (FSH) (rho=0.041, P=0.036), basal estradiol (E2) (rho=0.089, P<0.001), anti-Müllerian hormone (AMH) (rho=-0.057, P=0.004), antral follicle count (AFC) (rho=-0.053, P=0.007), E2 (rho=-0.080, P<0.001), number of oocytes retrieval (rho=-0.079, P<0.001) and progesterone (P)/E2 on hCG trigger day (rho=0.081, P<0.001). Conclusions Overall, there was only a rather weak correlation of free as well as total 25(OH)VitD with human endocrine and functional fertility parameters in women undergoing IVF/ICSI. Neither free nor total 25(OH)VitD seems to play a major role in human embryo implantation.